THE INFLUENCE OF INDONESIAN LANGUAGE LITERACY ON CRITICAL THINKING SKILLS OF GRADE XII STUDENTS OF SMAS AL-AZHAR MEDAN - Thalia Siti Zivana; Insan Fasyela; Sunarji Harahap; Rizqa Agniya Nasution; Rizki Ananda Amir; Safhira Rahmadhani Panggabean (CV. RADJA PUBLIKA, 2024)
This study raises the issue of students of class XII of SMA Unggulan Al-Azhar Medan still having difficulty optimizing literacy to support the development of critical thinking. This study aims to analyze the influence of Indonesian language literacy on the critical thinking skills of class XII students of SMA Unggulan Al-Azhar Medan. Using quantitative and survey methods, data from 133 students were collected through language and critical thinking tests. The results showed a significant positive relationship: students who were more fluent in Indonesian had better critical thinking skills. The study concluded that Indonesian language skills had a positive effect on the critical thinking skills of class XII students of SMA Unggulan Al-Azhar Medan. Meanwhile, suggestions from SMA Unggulan Al-Azhar Medan were encouraged to improve the Indonesian Language curriculum with innovative ways to improve students' critical thinking skills.